The communication skills of history teachers at the intermediate stage and their relationship to their educational competencies (Journal of the College of Basic Education, 2022)
The research included four chapters, the first chapter included the introduction and the importance of the research, as the importance of communication skills and educational competencies for the teacher was clarified. In the lack of the ability of many history teachers to use a variety of methods that are compatible with the nature of the subject, and the poor management of planning, implementation and evaluation of many history teachers. The problem of the current research lies in knowing whether there is a relationship between the communication skills of history teachers in the middle school Their educational competencies, and the objectives of the research included knowing the communication skills and educational competencies of history teachers in the middle stage, and the hypothesis of the research was that there is no statistically significant relationship between history teachers in communication skills and their educational competencies. As for the second chapter, it included theoretical studies, as the concept of communication skills and educational competencies was presented. Previous studies included the study of Jalal Muhammad and Haider Shaker as previous studies and related to the current study. The third chapter included field research procedures, as the two researchers used the one-group descriptive approach, and the research sample was the middle school history teachers in Baghdad Governorate, who numbered (151) teachers and schools. The form of communication skills and educational competencies was applied to the research sample. The fourth chapter included a presentation of the results of communication skills and educational competencies, as the results showed the presence of statistically significant differences and the results reached by the researchers were interpreted. As for the conclusions reached by the researchers were:1- Most of the history teachers at the intermediate stage in Baghdad governorate have a good amount of communication skills compared to the hypothetical average with which they were compared. And these skills need to be constantly developed.2- Most of the history teachers in the middle school have a good amount of educational competencies.3- There is a correlation between the research variables, which are communication skills and multiple intelligences.The most important recommendations were:1- Not allowing teachers of other specializations to teach history in the intermediate school.2- Preparing a guide for teachers of history in the intermediate stage that includes communication skills and educational competencies that were identified in this study in order to benefit from them by the teachers of the subject.3- The results of the current study can be used in building and designing similar educational programs for other educational stages and even for other educational materials.